Human exposure to neonicotinoid insecticides and the evaluation of their potential toxicity: An overview - Han, Wenchao; Tian, Ying; Shen, Xiaoming (Chemosphere (Oxford), 2018)
Neonicotinoid insecticides have become the fastest growing class of insecticides over the past few decades. The insecticidal activity of neonicotinoids is attributed to their agonist action on nicotinic acetylcholine receptors (nAChRs). Because of the special selective action on nAChRs in central nervous system of insects, and versatility in application methods, neonicotinoids are used to protect crops and pets from insect attacks globally. Although neonicotinoids are considered low toxicity to mammals and humans in comparison with traditional insecticides, more and more studies show exposure to neonicotinoids pose potential risk to mammals and even humans. In recent years, neonicotinoids and their metabolites have been successfully detected in various human biological samples. Meanwhile, many studies have focused on the health effects of neonicotinoids on humans. Our aims here are to review studies on human neonicotinoid exposure levels, health effect, evaluation of potential toxicity and to suggest possible directions for future research. •Neonicotinoids, as a novel class of insecticides, are used widely.•Neonicotinoids have been detected in human urine, serum, and hair.•In vivo/vitro studies suggested toxicity of neonicotinoids.•Large-scale epidemiological studies on human health effects are needed.